2021
DOI: 10.1186/s12903-021-01966-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of hormone replacement therapy in relieving oral dryness symptoms in postmenopausal women: a case control study

Abstract: Background To evaluate the efficacy of hormone replacement therapy in relieving oral symptoms in postmenopausal women presenting with genitourinary symptoms along with oral dryness. Methods A case–control study was conducted after selecting 60 postmenopausal women. Oral dryness status of all the patients was evaluated with the help of questionnaire related to oral dryness. These subjects were divided into case group and control group on the basis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Estrogen replacement therapy effectively alleviates menopausal symptoms such as xerostomia and hot flashes [4,31]. While the efficacy of hormone replacement therapy is undeniable, there are safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen replacement therapy effectively alleviates menopausal symptoms such as xerostomia and hot flashes [4,31]. While the efficacy of hormone replacement therapy is undeniable, there are safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 A recent case-control study Table 1 Effects of sex steroids in the mouth 3,26 and on immune system regulation. [26][27][28][29] conducted by Wang et al 16 found a reduction in dry mouth symptoms following HRT, but no improvements in burning sensations or waking up thirsty at night. However, the study had a small sample size and carried the possibility of bias through subjective questionnaire responses.…”
Section: Xerostomiamentioning
confidence: 98%
“…The cause of xerostomia is multifactorial, and currently no topical therapy has proven to be most effective in reducing the symptoms of dry mouth 13,15 . A recent case–control study conducted by Wang et al 16 . found a reduction in dry mouth symptoms following HRT, but no improvements in burning sensations or waking up thirsty at night.…”
Section: Salivary Glandsmentioning
confidence: 99%
“…Since damp surroundings are also necessary for the colonization and proliferation of bacteria in mouth areas, inadequate saliva can disrupt microbial stabilization to the advantage of diseases like Streptococcus mutants and Candida albicans (Contaldo et al,2020). Variations in the levels of steroid hormones have an effect on intestinal calcium absorption into the body, the menopausal period's decreasing estrogen levels lower intestinal calcium absorption (Wang et al,2021). Hormone replacement therapy (HRT), which is now available in a wide variety of compositions, methods of administration and drops, appears must be the most efficient therapy for menopausal signs.…”
Section: Menopause and Salivamentioning
confidence: 99%